VD_FINDINFO Jug / 2016 / 310 vom 9. März 2016 - VD Tribunal cantonal (2016)
MESURE THÉRAPEUTIQUE INSTITUTIONNELLE, PRÉSOMPTION D'INNOCENCE, TORT MORAL | 47 CO, 12 al. 2 CP, 59 al. 3 CP, 59 ch. 4 CP, 10 CPP (CH)